Avaliação de programas de seleção para a caprinocultura leiteira brasileira - Santos, Leonardo Hunaldo dos (2013)
This work aimed to evaluate the feasibility of a national breeding program for dairy goats. The genetic and economic gains for two selection schemes, one traditional that represents the overall Brazilian situation and the other using the progeny test, as proposed by the Breeding Program for Dairy Goats (CAPRAGENE) of Embrapa Goats and Sheep were compared. The economic impact of the use of bucks of the nucleus in commercial was evaluated in the traditional scheme. It was also examined the effects of intensity use of young breeding test for the scheme with progeny testing. Analyses were performed in ZPLAN, which uses a deterministic approach to estimate the genetic and economic gains for breeding programs. The traditional scheme with bucks selected in the nucleus of milk production and reproductive traits from their dams and the selection of does made with the same information for themselves and their dams, had no economic viability, not covering the costs of physical and human infrastructure for maintenance of the breeding program. The scheme using progeny tests of young bucks presented viability, with considerable genetic gains for the selection objective and the individual traits that make up this goal. The economic returns of the program outweigh the costs of the same, with a return on investment of about 20%. In this scheme, the trait of greater economic impact was milk yield followed by somatic cell count. The traditional scheme would only allow investment returns of the breeding program with high levels (>60%) for use of nucleus bucks commercial flocks. It is possible that this has no practical feasibility, principally due to the low use of artificial insemination in Brazil. The amount of use of young bucks should be between 10% and 15%. Major uses not promote substantial monetary gains to the selection objective and reduce the genetic profit the important traits as milk yield.